2020
DOI: 10.1177/1363461520916697
|View full text |Cite
|
Sign up to set email alerts
|

Treating immigrant patients in psychiatric emergency rooms

Abstract: We examine whether patient variables (geographic origin, gender, Spanish language proficiency) and subjective clinician aspects in emergency department psychiatric encounters (diagnostic certainty, clinician’s comfort level with patient) are associated with diagnosis and the use of coercive measures. Using a descriptive cross-sectional design, we recorded 467 visits (400 foreign-born and 67 native-born patients) in hospital psychiatry emergency rooms (ERs) in Barcelona between 2007 and 2015. We first assessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Proportional (non-significant) findings were reported in four studies where foreign nationals were more likely to receive restrictive practices [ 39 , 49 , 66 , 83 ]. No significant differences in ethnicity were reported in relation to findings in eleven studies [ 7 , 8 , 61 , 63 , 64 , 70 72 , 74 , 77 , 84 ].…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Proportional (non-significant) findings were reported in four studies where foreign nationals were more likely to receive restrictive practices [ 39 , 49 , 66 , 83 ]. No significant differences in ethnicity were reported in relation to findings in eleven studies [ 7 , 8 , 61 , 63 , 64 , 70 72 , 74 , 77 , 84 ].…”
Section: Resultsmentioning
confidence: 77%
“…In total, the studies contain findings based on 491,893 participants (255,342 females and 227,986 males) in the 34 primary studies and 98 studies comprising the four reviews. However, four primary studies failed to report the number of participants [ 57 60 ], whereas nine studies reported incomplete or no gender information (missing data: n = 8565) [ 1 , 39 , 57 63 ]. Reviews were not comparable by gender.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations